2017
DOI: 10.1080/0284186x.2017.1325004
|View full text |Cite
|
Sign up to set email alerts
|

Variability in axillary lymph node delineation for breast cancer radiotherapy in presence of guidelines on a multi-institutional platform

Abstract: The overall intra-institute and inter-institute agreement was moderate. Central lymph-node levels were the most critical and variability increased as the complexity of the patient's anatomy increased. These findings might have an effect on the interpretation of results from multicenter and even mono-institute studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In addition, the contouring process is burdened by time-consuming procedures which may slow the entire workflow. Apart from the introduction of atlas-based auto-contouring programs in the clinical practice, which proved to be beneficial in time reduction compared to the manual contouring [26], the possibility of expanding the role of CSRTs in the pre-planning phase represents a major asset. Several studies have already confirmed the great potential of CSRTs in normal tissue contouring in the head and neck and the pelvic districts [10][11][12][13]27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the contouring process is burdened by time-consuming procedures which may slow the entire workflow. Apart from the introduction of atlas-based auto-contouring programs in the clinical practice, which proved to be beneficial in time reduction compared to the manual contouring [26], the possibility of expanding the role of CSRTs in the pre-planning phase represents a major asset. Several studies have already confirmed the great potential of CSRTs in normal tissue contouring in the head and neck and the pelvic districts [10][11][12][13]27].…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses were conducted to evaluate volume parameters related to CT scan and MRI and interobserver variability compared to the benchmark [15,[25][26][27]. Descriptive statistics (mean, standard deviation, range of variability, median, 25th and 75th percentile) was calculated for GTV and duodenum, delineated on CT and MRI, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This personalized semi‐automated approach to radiotherapy treatment planning could become the future clinical standard, because the algorithm will take individual patient anatomy and treatment position into account once the anatomical landmarks are properly indicated. On top of that, several publications state that inter‐ and intra‐observer variability is high, even when delineations are made according to the same guidelines (as opposed to comparing delineations from different centers that might use slightly different guidelines) (Petersen et al ; Castro Pena et al ; Ciardo et al ). Automating the process of delineation is also expected to reduce this inter‐ and intra‐observer variability.…”
Section: Introductionmentioning
confidence: 99%